Simultaneous determination of N, N-dimethylformamide, N, N-dimethylacetamide and N-methyl-2-pyrrolidone in textiles by RP-HPLC. Issue 14 (21st March 2016) - Fu, Kejie; Bao, Qibei; Zhou, Wenlong; Yuan, Shuwei
Abstract : An environmentally compatible, rapid and sensitive RP-HPLC-DAD method was developed for the simultaneous detection of N -methyl-2-pyrrolidone, N, N -dimethylformamide, and N, N -dimethylacetamide in marketed textile products. Abstract : With the increasing establishment of regulations and standards limiting textile solvent residues in many countries and regions, residual solvents have become an important target of ecological textile testing. In this paper, a RP-HPLC method with diode array detection (DAD) was developed for the simultaneous detection of N -methyl-2-pyrrolidone, N, N -dimethylformamide, and N, N -dimethylacetamide in textiles after mechanical extraction in ultrapure water. The method exhibited good linearity for the three residual solvents, with correlation coefficients greater than 0.9999, LODs of 1.1–2.8 mg kg −1, and precision values below 5%. Different textile fiber matrixes afforded NMP recovery rates from 96.9 to 103.0%, with RSDs between 0.7 and 4.3%; DMF recovery rates from 97.0 to 103.0%, with RSDs between 0.9 and 4.9%; and DMAc recovery rates from 94.8 to 102.2%, with RSDs between 0.8 and 4.8%.